THE IMPLEMENTATION OF AUGMENTED REALITY-BASED LEARNING MEDIA ON CIVICS SUBJECT TO INCREASE LEARNING MOTIVATION OF ELEMENTARY SCHOOL STUDENTS - Dinda Firgiyana; Arief Cahyo Utomo (Jurnal Cakrawala Pendas, 2024)
This research is motivated by the low motivation of students to learn because the learning process tends to use traditional methods. The development of science and technology that is increasingly sophisticated can be utilized by teachers in using learning media. However, in reality, many teachers do not utilize the use of technology in teaching and learning activities. One of the media that can be used in the learning process is Augmented Reality-based media. The purpose of this study is to determine the implementation of Augmented Reality-based learning media to increase the learning motivation of VI grade students at SDN 01 Kenokorejo. This research employed a quantitative study with a quasi-experimental design using Single-Group Interupted Time-Series Design. This type of design only uses one class, namely the test class. The sample involved 14 students consisting of: 10 male students and 4 female students. The instrument used was a learning motivation questionnaire. Data collection techniques were through observation and questionnaires,. Prerequisite tests, namely normality test and homogeneity test and homegity test (T-test) through SPSS was used as the data analysis technique. The results of the univariate normality test were 0.16, which means > from 0.05, the data was declared "Normal". The univariate homogeneity test was 0.804, which means > from 0.05, it was declared "Homogeneous Data" and the homogeneity test (T-test) was 0.000 <0.05. This shows that there is a significant influence on the difference in the results of the learning motivation questionnaire. Based on the results of the study, it can be concluded that student learning motivation has increased. This is evident from the average score obtained by students from 68,14 to 83,92; so that the implementation of this learning media is effective in increasing student learning motivation.